Class size and learning: has India spent too much on reducing class size? - Datta, Sandip,Kingdon, Geeta Gandhi (IZA - Institute of Labor Economics, 2021)
This paper examines the efficacy of class-size reductions as a strategy to improve pupils' learning outcomes in India. It uses a credible identification strategy to address the endogeneity of class-size, by relating the difference in a student's achievement score across subjects to the difference in his/her class size across subjects. Pupil fixed effects estimation shows a relationship between class size and student achievement which is roughly flat or non-decreasing for a large range of class sizes from 27 to 51, with a negative effect on learning outcomes occurring only after class size increases beyond 51 pupils. The class-size effect varies by gender and by subject-stream. The fact that up to a class-size of roughly 40 in science subjects and roughly 50 in non-science subjects, there is no reduction in pupil learning as class size increases, implies that there is no learning gain from reducing class size below 40 in science and below 50 in non-science. This has important policy implications for pupil teacher ratios (PTRs) and thus for teacher appointments in India, based on considerations of cost-effectiveness. When generalised, our findings suggest that India experienced a value-subtraction from spending on reducing class-sizes, and that the US3.6 billion it spent in 2017-18 on the salaries of 0.4 million new teachers appointed between 2010 and 2017 was wasteful spending rather than an investment in improving learning. We show that India could save US 19.4 billion (Rupees 1,45,000 crore in Indian currency) per annum by increasing PTR from its current 22.8 to 40, without any reduction in pupil learning.
10419/236261
Keywords: Graue Literatur; class size; student achievement; India